2023
DOI: 10.1111/jog.15571
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between neonatal outcomes of labor and delivery with labor neuraxial analgesia and without analgesia: A propensity score‐matched study

Abstract: Aim This single‐center observational study aimed to investigate the association between labor neuraxial analgesia (LNA) and neonatal outcomes. Methods We conducted a retrospective cohort study at a tertiary perinatal center and included all vaginal deliveries performed between November 2015 and December 2021. Obstetric and neonatal outcomes were compared between deliveries with LNA (LNA group) and without analgesia (control group). Propensity score (PS) matching was used for statistical analysis. Results We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In multiparas, combined spinal-epidural analgesia (CSEA) provided superior analgesia and satisfaction compared to remifentanil patient-controlled analgesia (RPCA) [ 26 ]. After propensity score matching, Watanabe K and colleagues discovered that the nulliparous NA group exhibited a notably higher incidence of Apgar scores of 7 at both 1 and 5 min and had increased occurrences of meconium-stained amniotic fluid, while no significant difference in neonatal outcomes were observed in multiparous women [ 27 ]. Our study found that there was no significant difference in the amount and rate of PPH, the rate of transferred to ICU, postpartum stay ≥ 7d, the Apgar score at 1 and 5 min, the rate of neonatal transfer to NICU and the rate of meconium-stained amniotic fluid among the no-NA, early-NA and the late-NA multiparous women.…”
Section: Discussionmentioning
confidence: 99%
“…In multiparas, combined spinal-epidural analgesia (CSEA) provided superior analgesia and satisfaction compared to remifentanil patient-controlled analgesia (RPCA) [ 26 ]. After propensity score matching, Watanabe K and colleagues discovered that the nulliparous NA group exhibited a notably higher incidence of Apgar scores of 7 at both 1 and 5 min and had increased occurrences of meconium-stained amniotic fluid, while no significant difference in neonatal outcomes were observed in multiparous women [ 27 ]. Our study found that there was no significant difference in the amount and rate of PPH, the rate of transferred to ICU, postpartum stay ≥ 7d, the Apgar score at 1 and 5 min, the rate of neonatal transfer to NICU and the rate of meconium-stained amniotic fluid among the no-NA, early-NA and the late-NA multiparous women.…”
Section: Discussionmentioning
confidence: 99%